2006
DOI: 10.1152/ajpcell.00465.2005
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine loop between TGF-β1 and IL-1β through Smad3- and ERK-dependent pathways in rat pancreatic stellate cells

Abstract: Pancreatic stellate cells (PSCs) are activated during pancreatitis and promote pancreatic fibrosis by producing and secreting ECMs such as collagen and fibronectin. IL-1beta has been assumed to participate in pancreatic fibrosis by activating PSCs. Activated PSCs secrete various cytokines that regulate PSC function. In this study, we have examined IL-1beta secretion from culture-activated PSCs as well as its regulatory mechanism. RT-PCR and ELISA have demonstrated that PSCs express IL-1beta mRNA and secrete IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 33 publications
3
64
0
1
Order By: Relevance
“…Several studies have suggested that ERK is able to modulate IL-1␤ enhancement of TGF␤1 expression, since the MEK-1 inhibitor PD98059 can reverse the stimulation of TGF␤1 by IL-1␤ (37). In our studies, using the more specific MEK inhibitor U0126, no effect of ERK-1/2 phosphorylation blockade was observed on the levels of TGF␤RII mRNA or protein, which suggests that another pathway is involved.…”
Section: Discussionsupporting
confidence: 44%
“…Several studies have suggested that ERK is able to modulate IL-1␤ enhancement of TGF␤1 expression, since the MEK-1 inhibitor PD98059 can reverse the stimulation of TGF␤1 by IL-1␤ (37). In our studies, using the more specific MEK inhibitor U0126, no effect of ERK-1/2 phosphorylation blockade was observed on the levels of TGF␤RII mRNA or protein, which suggests that another pathway is involved.…”
Section: Discussionsupporting
confidence: 44%
“…All these signalling molecules have previously been identified as key components of the intracellular network triggering PSC activation [14,15,25] . Furthermore, ET-1 significantly stimulated expression of two cytokines that have previously been suggested as autocrine enhancers of PSC activation, IL-1β and IL-6 [18,19] . Since both cytokines are well-established pro-inflammatory mediators, our data also implicate, for the first time, ET-1 in the enhancement of local inflammatory reactions in the pancreas.…”
Section: Discussionmentioning
confidence: 85%
“…Following liver damage in CP, acinar, duct, endothelial, and inflammatory cells all release a large amount of inflammatory mediators, such as platelet-derived growth factor, transforming growth factor-beta (TGF-β), interleukin-1 (IL-1), tumor necrosis factor-alpha (TNF-α), and so on, resulting in PSC activation, aggregation, and proliferation Aoki et al, 2006;Habisch et al, 2010). Finally, the cell morphology and function of PSCs are changed and self-activated to promote matrix proliferation (Apte et al, 1998Phillips et al, 2003).…”
Section: Introductionmentioning
confidence: 99%